Kriegsliteratur Dr. Jos. Klüber / Mathilde Ade. - Ade, Mathilde (1877-1953) ([Wydawca nieznany], 1936)
Pielęgniarka opatruje rękę Kupidyna, obok stoi armata a za nią diabeł. Napis: Kriegsliteratur Dr. Jos. Klüber.